2009
DOI: 10.1055/s-0029-1220331
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Platelet Procoagulant Mechanisms in Patients with Bleeding Disorders

Abstract: Activated platelets contribute to the arrest of bleeding by forming aggregates at sites of vascular injury and by providing a surface for assembling enzyme complexes involved in fibrin formation (platelet procoagulant activity; PCA). Impairment in the latter property of platelets has been observed in some disorders of hemostasis. In Scott syndrome, there is a defect in membrane vesiculation and in the surface expression of phosphatidylserine (PS), the phospholipid that is necessary for assembling the factor VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…13 A contribution of GPIb-V-IX has long been postulated on the grounds of the decreased prothrombin consumption observed in Bernard-Soulier patients. [14][15][16][17] The evaluation of procoagulant activity in Bernard-Soulier platelets initially led to divergent conclusions. 16,[18][19][20][21][22][23] Whereas decreased thrombin generation was reported by some authors, 18,23 increased thrombin generation 19 and PS exposure was observed by others in activated and resting platelets.…”
Section: Introductionmentioning
confidence: 99%
“…13 A contribution of GPIb-V-IX has long been postulated on the grounds of the decreased prothrombin consumption observed in Bernard-Soulier patients. [14][15][16][17] The evaluation of procoagulant activity in Bernard-Soulier platelets initially led to divergent conclusions. 16,[18][19][20][21][22][23] Whereas decreased thrombin generation was reported by some authors, 18,23 increased thrombin generation 19 and PS exposure was observed by others in activated and resting platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In Scott syndrome, abnormal platelet procoagulant activity can be measured using the serum prothrombin time or with the serum prothrombin consumption index [108,109]. The diagnosis of Scott syndrome can also be made using flow cytometry.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Pathophysiologisch ist bei diesen Sekretionsstörungen insbesondere die Amplifikationsphase der thrombozytären Gerinnung gestört, weiterhin sind plasmatische Störungen durch verminderte Faktorenfreisetzung (z.B. Faktor V) oder gesteigerte Freisetzung von fibrinolytischen Faktoren (Quebec-Thrombozytopathie) beschrieben [4,5,7]. Sekretionsstörungen repräsentieren zahlenmäßig die wahrscheinlich bedeutendste Gruppe thrombozytopathischer Störungen, aufgrund der großen interindividuellen Variabilität und der diagnostischen Limitierungen ist die Prävalenz jedoch weitgehend unklar.…”
Section: Störungen Der Thrombozytären Sekretionunclassified